Assessing the Curriculum Viability Inhibitors in an Undergraduate Medical Curriculum from the Perspective of Teaching Faculty - Muhammad Ammar Qasim; Qurat-; Gulrez Amin; Khadijah Mukhtar; Mahnoor Mukhtar; Rehan Ahmed Khan (University of Lahore, 2024)
Objective: Curriculum viability refers to the sustainability and effectiveness of an educational curriculum. This study was done to assess curriculum viability inhibitors in an undergraduate medical curriculum at the University College of Medicine and Dentistry, Lahore, Pakistan. Methodology: This qualitative exploratory study was conducted from November 2023 till March 2024, including 8 faculty members with more than 5 years ofexperience from both the clinical and basic sciences of undergraduate MBBS program at UCMD. The questionnaire filled in before conducting FGD contained 6 viability inhibitors, which included Educational Program Inhibitors; Disciplinary Cultural Inhibitors; Social Interaction Inhibitors; Institutional Policies Inhibitors; Communication Practices inhibitors; and Faculty Involvement Inhibitors. There were total of 25 items collectively under these six inhibitors. The FGD that followed was conducted for two hours, involving two main interviewers, two observers and one interpreter for recording the data. Results: All of the 8 participants of the cohort unanimously agreed that there were no issues in the educational program and the curriculum was designed according to the major outcomes of the institute and was being followed in letter and inspirit. However, they highlighted 3 out of 25 items which according to them were not effective.  First two items belonged to institutional policies inhibitors (item 12, and 15), and one belonged to faculty involvement inhibitors (item 25). The data underwent rigorous thematic analysis,involving the meticulous manual examination of transcribed data. Conclusion: While the faculty was generally satisfied with the curriculum, minor challenges exist that can be addressed through collaborative SWOT analysis meetings with stakeholders. The report emphasized the importance of continuous improvement and stakeholder engagement for a sustainable and responsive curriculum.